B-type Natriuretic Peptide as an Index of Symptoms and Severity of Chronic Rheumatic Mitral Regurgitation - Abdel Fattah, Eman M. (Heart Views, 2016)
BACKGROUND: The most common causes of severe mitral regurgitation (MR) in developing countries are rheumatic heart disease. The plasma level of B-type natriuretic peptide (BNP) is known to increase with left ventricular (LV) dysfunction. AIM OF THE WORK: To study BNP level as an index of symptoms and severity of chronic rheumatic MR. PATIENTS AND METHODS: One hundred and forty patients with rheumatic MR and LV ejection fractions (EFs) of >55% underwent assessment of symptoms, transthoracic echocardiography, and measurement of BNP. Results: The level of BNP rose with increasing left atrium (LA) dimensions and volumes, LV dimensions and volumes, echocardiographic parameters of MR severity (width of the vena contracta, regurgitation jet area, effective regurgitation orifice area, and regurgitant volume), and E waves. RESULTS: BNP was significantly higher in patients with severe MR compared with moderate and mild MR (P < 0.001), and using cutoff point of 61 pg/mL mm had 97% sensitivity and 89% specificity for predicting patients with severe MR (0.99, 95% confidence interval [CI] 0.9–1). BNP was significantly higher in patients with New York Heart Association (NYHA III) compared with NYHA II, I and asymptomatic patients (P < 0.001) and using cutoff point of 53 pg/mL had 97% sensitivity and 87% specificity for predicting symptomatic patients with symptomatic MR (0.81, 95% CI 0.70–0.92). CONCLUSIONS: BNP level increase with increasing severity of rheumatic MR and are higher in symptomatic compared to asymptomatic patients, even in the presence of normal EF%.